A 40Ar/39Ar and U/Pb isotopic study of the Ilímaussaq complex, South Greenland: Implications for the 40K decay constant and for the duration of magmatic activity in a peralkaline complex - Krumrei, TV; Marks, MAW; Markl, G.; VILLA, IGOR MARIA (Chemical Geology, 2006)
Magmatism in the Gardar Province, South Greenland, is related to two main rifting events at 1280 Ma and 1180 to 1140 Ma. Little is known about the duration of the magmatic activity in a specific complex. The Ilímaussaq intrusion belongs to the second period of rifting and comprises an extraordinary diversity of granitic and syenitic rock types, which intruded and fractionated in three successive magmatic events. As the intrusion contains some of the most evolved, incompatible element-rich rocks on Earth, it was chosen for a detailed geochronological study to quantify the duration of melt production, intrusion, fractionation and cooling. Amphiboles, which are abundant in all rock types, including pegmatites and late magmatic veins, were dated using the 40 Ar/ 39 Ar technique. Since the solidus temperature of the most evolved melts is below the closure temperature of amphibole, and no later heating event occurred, the 40 Ar/ 39 Ar ages reflect the magmatic crystallisation and can be used to determine the duration of igneous differentiation. The 40 Ar/ 39 Ar plateau ages range between 1142.6 ± 2.2 Ma and 1152.3 ± 3.7 Ma using the Steiger and Jäger [Steiger, R.H. and Jäger, E., (1977). Subcommision on Geochronology: Convention on the use of decay constants in geo- and cosmochronology. Earth Planet. Sci. Lett. 36, 359-362.] 40 K decay constant. These ages are younger than an U-Pb age of 1160 ± 5 Ma on baddeleyite from the first magma batch. Our results indicate that the 40 K decay constant of Steiger and Jäger may be too high; a lambda similar to that proposed by Kwon et al. [Kwon, J., Min, K., Bickel, P. and Renne, P.R., (2002). Statistical methods for jointly estimating decay constant of 40 K and age of a dating standard. Math. Geol. 34, 457-474.] is required to make the 40 Ar/ 39 Ar match the U-Pb age. © 2005 Elsevier B.V. All rights reserved. Magmatism in the Gardar Province, South Greenland, is related to two main rifting events at 1280 Ma and 1180 to 1140 Ma. Little is known about the duration of the ...